Effects of extenders on the functional activity of chilled canine spermatozoa during prolonged storage - Y. V. Litvinchuk; V. V. Kovpak; O. S. Kovpak; S. S. Derkach; O. A. Valchuk; Y. V. Zhuk (Regulatory Mechanisms in Biosystems, 2025)
Preserving the quality and providing a high fertile capacity of spermatozoa are some of the main objectives of successful fertilization of dogs. Insemination using chilled semen produces higher pregnancy parameters and larger litters, compared with using frozen semen. Therefore, this practice is in high demand. Nevertheless, there is an issue of prolonged storage of chilled semen, especially relevant during transportation to long distances. Considering that high-quality parameters of spermatozoa directly depend on a medium in which they are stored, the objective of this study was determining the effects of different types of extenders on the functional characteristics of chilled canine semen during prolonged storage. We studied the effects of the extenders on the motility, ability to move in a straight line, integrity of the membrane, and DNA fragmentation of canine spermatozoa. The second fraction of ejaculate was collected from five dogs using the masturbation method. The semen was centrifuged to achieve settlement of the spermatozoa and remove the plasma. To the spermatozoa sediment, one of the following extenders was added, which had been heated up to the room temperature: Т – TRIS + citric acid + glucose (base content); Т-EG – base content + egg yolk; Т-BSA – base content + BSA; T-EDTA – base content + EDTA in a calculation of 150×10 6 spermatozoa in 5 cm 3 of extender. After pipetting, the samples were cooled to 4 °C with subsequent daily monitoring until the tenth day of storage. The results of the study revealed that the extender Т-BSA provided the highest parameters of the general motility and straight-line movement of the spermatozoa over the storage period. In the descending order, the effectiveness of extenders in preserving the sperm motility at a 50% level was as follows: Т-BSA (7 days); T and T-EDTA (6 days); Т-EG (5 days). At the same time, according to the percentage of gametes with straight-line movements, the results were as follows: Т-BSA (7 days); T and Т-EG (5 days); T-EDTA (4 days). The percentage of spermatozoa with damaged membrane over the period of storage increased (by 13.4 – 16 .0 %, compared with day zero), although no effect of the extender composition on this parameter was observed. The level of DNA fragmentation in the chilled canine sperm increased insignificantly (up to 0.4% by day 10) over the storage period, without significant effect of the extender on this parameter. In summary, the extender Т-BSA demonstrated the highest effectiveness in the preservation of sperm motility at a 4 °C temperature, maintaining the general motility at the level of 37.4 ± 5.9% and the straight-line move ment at the level of 31.2 ± 6.6 % on day 10 of storage. This allows us to consider Т-BSA an optimal compos i tion for long storage of dog semen in a chilled state.